1999
DOI: 10.1210/endo.140.2.6533
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Estrogen Receptor-β and Estrogen Receptor-α in the Rat Ovary

Abstract: Immunohistochemical localization of two estrogen receptor (ER) subtypes, ER beta and ER alpha, was performed in neonatal, early postnatal, immature, and adult rats to determine whether ER alpha and ER beta are differentially expressed in the ovary. ER beta and ER alpha were visualized using a polyclonal anti-ER beta antibody and a monoclonal ER alpha (ID5) antibody, respectively. Postfixed frozen sections and antigen-retrieved paraffin sections of the ovary revealed nuclear ER beta immunoreactivity (IR) in gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(46 citation statements)
references
References 39 publications
4
41
0
1
Order By: Relevance
“…Genes significantly up-regulated in this pathway were CTBP2, ESR1, GTF2H1, GTF2H2, MAP2K1, NCOA1, NCOA3, PCQAP, PHB2, POLR2C, POLR2J, RBM9, TAF3, TAF4 and 4B, TAF5, TAF6, TAF12, and TBP. Recent studies in knockout models for aromatase have shown that estrogen is not required for the generation of preimplantation embryos (34); our study, however, in agreement with previous reports (35,36) suggests that some genes associated with the ER pathways are indeed transcribed in the oocyte, perhaps in response to hormonal stimulation during folliculogenesis and oocyte maturation. It remains to be determined whether the ER pathway has a role during preimplantation development in human embryos.…”
Section: Functional Annotation Of Genes Overexpressed In the Human Oosupporting
confidence: 93%
“…Genes significantly up-regulated in this pathway were CTBP2, ESR1, GTF2H1, GTF2H2, MAP2K1, NCOA1, NCOA3, PCQAP, PHB2, POLR2C, POLR2J, RBM9, TAF3, TAF4 and 4B, TAF5, TAF6, TAF12, and TBP. Recent studies in knockout models for aromatase have shown that estrogen is not required for the generation of preimplantation embryos (34); our study, however, in agreement with previous reports (35,36) suggests that some genes associated with the ER pathways are indeed transcribed in the oocyte, perhaps in response to hormonal stimulation during folliculogenesis and oocyte maturation. It remains to be determined whether the ER pathway has a role during preimplantation development in human embryos.…”
Section: Functional Annotation Of Genes Overexpressed In the Human Oosupporting
confidence: 93%
“…S oon after the discovery of estrogen receptor ␤ (ER␤) in 1996 (1), Sar and Welsch (2) showed that there is high expression of ER␤ in the nuclei of granulosa cells and suggested that ER␤ mediates some effects of estrogen action in the regulation of growth and maturation of ovarian follicles. Studies on mice that do not synthesize estrogen (aromatase knockout mice) have revealed that estrogen is essential for ovulation (3) but not for granulosa cell proliferation.…”
mentioning
confidence: 99%
“…During the juvenile to pubertal stages, HPG axis are central to the dramatic neuroendocrine changes in the process of maturation, including changes in E 2 positive/negative feedback system and gonadotropin and their receptor levels (Picut et al, 2015). The difference in the effects of EGME among juvenile, pubertal, and mature rats is possibly due to the differential effects of EGME on the HPG axis or the difference in the sensitivity or regulation of the hormonal effects of E 2 or P4 on the reproductive organs during sexual maturation, with the complication of secondary effect of growth retardation and delay in the onset of puberty (Ohta et al, 1996;Picut et al, 2015;Sar and Welsch, 1999). The highest dose, at 300 mg/kg of EGME, showed severe growth retardation with more than 30% lower body weight compared to controls as well as significant delay in puberty onset, and disruption of estrous cycle.…”
Section: Discussionmentioning
confidence: 99%